The economic effects of the CAP reform on Aragonese sheep farms - Manrique E.; Zamudio A.; Olaizola A.M. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The last CAP reform decouples subsidies from production and is, therefore, the most radical reform that has been implemented to date. This reform is generating many uncertainties in the sector and is perceived as a factor that will speed up structural changes. Aragon is an important sheep-farming region in Spain, both in terms of sheep census and the modernity and dynamism of the sector. Based on a sample of sheep farmers located in Aragon belonging to the Spanish Farm Accountancy Data Network, the implications of the reform have been simulated at farm level, considering several scenarios.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)